Magnetism and spin dynamics in room-temperature van der Waals magnet Fe5GeTe2. (13th September 2021) - Alahmed, Laith; Nepal, Bhuwan; Macy, Juan; Zheng, Wenkai; Casas, Brian; Sapkota, Arjun; Jones, Nicholas; Mazza, Alessandro R; Brahlek, Matthew; Jin, Wencan; Mahjouri-Samani, Masoud; Zhang, Steven S.-L.; et al.
Abstract: Two-dimensional van der Waals (vdWs) materials have gathered a lot of attention recently. However, the majority of these materials have Curie temperatures that are well below room temperature, making it challenging to incorporate them into device applications. In this work, we synthesized a room-temperature vdW magnetic crystal Fe5 GeTe2 with a Curie temperature T c = 332 K, and studied its magnetic properties by vibrating sample magnetometry (VSM) and broadband ferromagnetic resonance (FMR) spectroscopy. The experiments were performed with external magnetic fields applied along the c -axis ( H ∥ c ) and the ab -plane ( H ∥ ab ), with temperatures ranging from 300 to 10 K. We have found a sizable Landé g -factor difference between the H ∥ c and H ∥ ab cases. In both cases, the Landé g -factor values deviated from g = 2. This indicates contribution of orbital angular momentum to the magnetic moment. The FMR measurements reveal that Fe5 GeTe2 has a damping constant comparable to Permalloy. With reducing temperature, the linewidth was broadened. Together with the VSM data, our measurements indicate that Fe5 GeTe2 transitions from ferromagnetic to ferrimagnetic at lower temperatures. Our experiments highlight key information regarding the magnetic state and spin scattering processes in Fe5 GeTe2, which promote the understanding of magnetism in Fe5 GeTe2, leading to implementations of Fe5 GeTe2 based room-temperature spintronic devices.